How to price the unbundled local loop in the transition from copper to fiber access networks? - Karl-Heinz Neumann; Ingo Vogelsang (International Telecommunications Society (ITS), 2013)
In many countries worldwide access networks are in the transition from copper to fiber access. During the transition phase copper and fiber networks are operated in parallel. All regulators facing this situation of technological change have to decide how to price unbundled access to the copper loop in this transition phase. Should they keep the usual forward looking long-run incremental cost standard charge, or should they move to some different approach? The authors propose to price copper access based on the modern equivalent asset (MEA) of fiber access. Since fiber access is superior to copper access, the cost of fiber access (as a basis for pricing copper access) should, however, be corrected by the performance delta between copper and fiber access. Instead of using quality of service (QoS) differences, the authors determine the performance delta based on the market valuation of services provided over the copper and fiber access represented by the end-user prices of services and corrected by cost differences downstream of the access provision. Under this approach an access seeker becomes indifferent (on the margin) between using the copper or the fiber access network and wholesale pricing (or regulation) becomes competitively neutral towards technology choice between copper and fiber access and does not distort the platform competition towards cable. To test its practicability numerical simulations of the approach are performed by means of a quantitative competition model. The model analysis suggests that the approach leads to unique and robust results. Its main conclusion is that the method tends to be conservative relative to the theoretical case of pure vertical product differentiation, meaning that the measured performance delta underestimates the theoretical performance delta.
Keywords: 330; Copper access; Fiber to the home (FTTH); Modern equivalent asset; Long-run incremental costs (LRIC); Performance delta